Effects of fire frequency on plant communities and landscape pattern in the Massif des Aspres (southern France) - Trabaud, L; Galtié, J F (Landscape Ecology, 1996)
Fire frequency can affect pattern and diversity in plant communities and landscapes. We had the opportunity to study changes due to recurring wildfires on the same sites over a period of 50 years in the "Massif des Aspres" (southern France). The study was carried out in areas occupied by Quercus suber and Q. ilex series. A comparison of historical and cartographical documents (vegetation maps covering a 50 year interval and an accurate map of major wildfires during this period) allowed us to determine the changes occurring over time with or without fire action. Plant communities were grouped into three main vegetation types: forests, treed shrublands and shrublands. The passage of three successive wildfires on the same site led to a decrease in for- est areas and an increase in shrublands; however, shrublands were already present before the first fire of the period under consideration. Less frequent fire occurrence induced more complex heterogeneity and greater landscape diversity. In the study region as a whole, with or without fire action, a significant decrease in forest surfaces was recorded, whereas there was an increase of unforested communities such as treed shrublands and shrublands. In some parts of the Massif fires increased the homogeneity of the landscape, in other parts they created a greater heterogeneity and diversity of plant communities.
Keywords: aspres; fire; landscape diversity; Quercus ilex; Quercus suber; Southern France